1995
DOI: 10.7326/0003-4819-123-5-199509010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol Dosage in the Prevention of Nonsteroidal Anti-inflammatory Drug-Induced Gastric and Duodenal Ulcers: A Comparison of Three Regimens

Abstract: Misoprostol, 200 micrograms twice or three times daily, offers substantial protection against gastric and duodenal ulcers in patients receiving long-term NSAID therapy. These dosages were better tolerated than the currently approved regimen of 200 micrograms four times daily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(75 citation statements)
references
References 0 publications
1
71
0
2
Order By: Relevance
“…Numerous RCTs have been carried out, both in normal volunteers and in patients with arthritic disorders, to evaluate the efficacy of coadministration of various agents for the prevention of both NSAID-related, nonulcer gastropathy and GU and DU (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Generally, these have shown that concomitant administration of the prostaglandin E1 analog misoprostol along with various NSAIDs can prevent both GU and DU (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23); that the proton pump inhibitor (PPI) (24 -26) omeprazole reduces GU and prevents DU; and that H2 receptor antagonists are effective in preventing DU but not GU (27,28).…”
Section: Concurrent Use Of Anticoagulantsmentioning
confidence: 99%
“…Numerous RCTs have been carried out, both in normal volunteers and in patients with arthritic disorders, to evaluate the efficacy of coadministration of various agents for the prevention of both NSAID-related, nonulcer gastropathy and GU and DU (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Generally, these have shown that concomitant administration of the prostaglandin E1 analog misoprostol along with various NSAIDs can prevent both GU and DU (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23); that the proton pump inhibitor (PPI) (24 -26) omeprazole reduces GU and prevents DU; and that H2 receptor antagonists are effective in preventing DU but not GU (27,28).…”
Section: Concurrent Use Of Anticoagulantsmentioning
confidence: 99%
“…64 The method of randomisation was reasonably well described in only two studies 43,64 and incompletely 64 the rest were all 'unclear'.…”
Section: Study Qualitymentioning
confidence: 99%
“…Extra outcome data were provided for only eight of these studies. [37][38][39][40][41][42][43][44] Five offered data on outcomes not previously recorded for that study, five offered information that no events had occurred in some outcomes and four offered data differing from those already collected from the study publication(s). Replies about the same eight studies and one further study 45 provided extra information on study quality (method of randomisation, allocation concealment, etc.…”
Section: Contact With Trialistsmentioning
confidence: 99%
“…As pharmaceutical adjuvants to this program, TTM 275,277 and high-dose aspirin, a salicylate salt, or salsalate (∼4.5-6 g daily in multiple divided doses, along with misoprostol, 200 mg twice daily or 3 times daily for GI protection if aspirin is used 328 ) are recommended, under careful physician supervision. Lowdose aspirin, for patients not using high-dose aspirin, can be recommended as an antithrombotic measure.…”
Section: Overviewmentioning
confidence: 99%